Narrative Engagement in Problem-Based Learning: Enhancing Students’ Maharah Qira’ah through Contextual Meaning-Making - Fridila Zasyiva; Musli Musli; Mustar Mustar; Muhammad Ahmad Abdul Ghoffar; Tata Frarisia; Putri Hardiyanti (Yayasan Adra Karima Hubbi, 2026)
Background. Arabic reading skills (Mah?rah Qir?’ah) are crucial in language acquisition, but traditional teacher-centered instruction at Madrasah Tsanawiyah often leads to passive engagement and limited contextual comprehension. Purpose. This study investigates the impact of the Problem-Based Learning (PBL) model on students’ Mah?rah Qir?’ah, focusing on the narrative engagement and meaning-making processes that influence learning outcomes. Method. A mixed-method explanatory sequential design was employed. The quantitative component used a quasi-experimental pre-test and post-test with 20 Madrasah Tsanawiyah students, analyzed using descriptive statistics and a paired sample t-test. The qualitative component involved semi-structured interviews with six purposively selected students, analyzed thematically. Results. Quantitative results showed a significant improvement in Mah?rah Qir?’ah, with mean scores rising from 59.5 to 92.5 (p < 0.05). Thematic analysis revealed three key themes: a shift from passive decoding to active meaning construction, the role of collaborative group discussions in comprehension, and linguistic barriers as differentiating factors. Conclusion. The findings suggest that PBL’s effectiveness is enhanced through narrative engagement, as students construct meaning via reading, discussion, and interpretation. These results position PBL as an effective, contextually responsive approach for Arabic language education. Educators are encouraged to incorporate vocabulary scaffolding to promote equitable participation.